2017
DOI: 10.1371/journal.pone.0170024
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Drug Use among Chinese MSM and Transgender Individuals: Results from a National Online Cross-Sectional Study

Abstract: BackgroundRecreational drug use has increased considerably among Chinese men who have sex with men (MSM). The phenomenon has the potentially to increase HIV transmission among Chinese MSM. The aims of this study were: 1) to investigate the prevalence of recreational drug use among Chinese MSM, and 2) to explore the correlation between gay smartphone based sex-seeking applications (gay apps), HIV/STIs testing, group sex, commercial sex, sexual roles and poppers use among Chinese MSM.MethodsMSM who were born bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 27 publications
6
31
3
Order By: Relevance
“…Consistent with results from the coastal metropolises [ 12 – 14 ], the current study found poppers was the most prevalent recreational drug among MSM in southwestern China. Of the 1122 participants, 270 (24.1%) reported using poppers in their life time, which was higher than reports in Shenyang (19.2%) [ 13 ] and Changsha (16.1%) [ 14 ], but lower than the 3-month use rate (26.8%) among MSM in Beijing [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with results from the coastal metropolises [ 12 – 14 ], the current study found poppers was the most prevalent recreational drug among MSM in southwestern China. Of the 1122 participants, 270 (24.1%) reported using poppers in their life time, which was higher than reports in Shenyang (19.2%) [ 13 ] and Changsha (16.1%) [ 14 ], but lower than the 3-month use rate (26.8%) among MSM in Beijing [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies from western countries reported that methamphetamine or ecstasy were the most commonly used drugs among MSM [ 8 , 9 ], which was consistent with findings in earlier years of China [ 10 , 11 ]. In recent years, several studies with large sample size approached the issue of drug use and found poppers (amyl nitrites) had outweighed methamphetamine or ecstasy and become the most popular recreational drug among MSM in coastal metropolises of China [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the risks of HCV transmission among our included patients could not be definitely identified. While we used syphilis as a surrogate for high‐risk behaviours for HCV transmission, we were not able to examine the role of ‘chemsex’, in which parenteral illicit drugs might have been concurrently used in patients with HCV reinfection in Taiwan . Fourth, we did not perform phylogenetic analysis of HCV strains identified in the first episode and the subsequent episodes from the same patients with reinfections …”
Section: Discussionmentioning
confidence: 99%
“…By the end of 2017, there were 2.6 million drug addicts nationwide [22]. The rate of RD use among China MSM ranged from 24.1 to 77.1% [23][24][25]. Thus, it is imperative to understand the relationship between polydrug use and recent HIV infection among Chinese MSM to develop "tailored" interventions that control RD abuse speci cally in the hope of mitigating the HIV epidemic.…”
Section: Introductionmentioning
confidence: 99%